Fc Engineering for Developing Therapeutic Bispecific Antibodies and Novel Scaffolds - Liu, Hongyan; Saxena, Abhishek; Sidhu, Sachdev S.; Wu, Donghui (Frontiers in Immunology, 2017)
Therapeutic monoclonal antibodies [mAbs] have become molecules of choice to treat autoimmune disorders, inflammatory diseases and cancer. Moreover, bispecific/multispecific antibodies that target more than one antigen or epitope on a target cell or recruit effector cells [T cell, natural killer (NK) cell or Macrophage cell] towards target cells have shown great potential to maximize the benefits of antibody therapy. In the past decade, many novel concepts to generate bispecific and multispecific antibodies have evolved successfully into a range of formats from full bispecific immunoglobulin gammas [IgGs] to antibody fragments. Impressively, antibody fragments such as bispecific T-cell engager [BiTE], bispecific killer cell engager [BiKE], trispecific killer cell engager [TriKE], tandem diabody [Tandab] and dual-affinity-retargeting [DART] are showing exciting results in terms of recruiting and activating self-immune effector cells to target and lyse tumor cells. Promisingly, Fc antigen binding fragment [Fcab] and monomeric antibody or half antibody may be particularly advantageous to target solid tumours owing to their small size and thus good tissue penetration potential while, on the other hand, keeping crystallizable fragment [Fc] related effector functions such as antibody-dependent cellular cytotoxicity [ADCC], complement-dependent cytotoxicity [CDC], antibody dependent cell-mediated phagocytosis [ADCP] and extended serum half-life via interaction with neonatal Fc receptor [FcRn]. This review, therefore, focuses on the progress of Fc engineering in generating bispecific molecules and on the use of small antibody fragment as scaffolds for therapeutic development.